Drug survival of biologics in treating psoriasis: a meta-analysis of real-world evidence - Lin, Pei-Tzu; Wang, Shu-Hui; Chi, Ching-Chi (Scientific reports, 2018)
Drug survival of biologics represents their real-world effectiveness and safety. We conducted a meta-analysis of real-world evidence on the drug survival of biologics in treating psoriasis. We searched the PubMed, CENTRAL, and EMBASE databases from inception to 7th October 2017 for studies reporting the annual drug survival for at least 1 year. Two authors independently screened and selected relevant studies, and assessed their risk of bias. A third author was available for arbitrating discrepancies. We conducted a random-effects model meta-analysis to obtain the respective pooled drug survival from year 1 to 4. We conducted subgroup analysis on biologic-naïve subjects, discontinuation for loss of efficacy and adverse effects. We included 37 studies with 32,631 subjects. The drug survival for all biologics decreased with time, dropping from 66% at year 1 to 41% at year 4 for etanercept, from 69% to 47% for adalimumab, from 61% to 42% for infliximab, and from 82% to 56% for ustekinumab. Ustekinumab was associated with the highest drug survival in all and biologic-naïve subjects. Etanercept was associated with the lowest drug survival and was most commonly discontinued for loss of efficacy. Infliximab was most frequently associated with discontinuation for adverse effects. Clinicians may use this study as a reference in treating psoriasis.